2011
DOI: 10.1152/japplphysiol.00711.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hemodynamics and vascular reactivity in asphyxiated term lambs resuscitated with 21 and 100% oxygen

Abstract: An increase in oxygen tension is an important factor in decreasing pulmonary vascular resistance (PVR) at birth. Birth asphyxia results in acidosis and increased PVR. We determined the effect of resuscitation with 21 vs. 100% O(2) on pulmonary hemodynamics, pulmonary arterial (PA) reactivity, and oxidant stress in a lamb model of in utero asphyxia. Term fetal lambs were acutely asphyxiated by intrauterine umbilical cord occlusion for 10 min resulting in acidosis (pH 6.96 ± 0.05 and Pco(2) 103 ± 5 Torr), bradyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 36 publications
1
44
0
2
Order By: Relevance
“…[216][217][218][219][220][221][222][223] 222 One demonstrated more rapid restoration of cerebral blood flow but no difference in histologic brain injury scores. 224 For the critical outcome of oxidative injury, we found 10 animal studies reported on oxidative injury with varying results 212,213,216,[219][220][221][222][223][225][226][227] (very-low-quality evidence, downgraded for potential bias, inconsistency, and indirectness).…”
Section: Consensus On Sciencementioning
confidence: 93%
See 2 more Smart Citations
“…[216][217][218][219][220][221][222][223] 222 One demonstrated more rapid restoration of cerebral blood flow but no difference in histologic brain injury scores. 224 For the critical outcome of oxidative injury, we found 10 animal studies reported on oxidative injury with varying results 212,213,216,[219][220][221][222][223][225][226][227] (very-low-quality evidence, downgraded for potential bias, inconsistency, and indirectness).…”
Section: Consensus On Sciencementioning
confidence: 93%
“…For the critical outcome of ROSC, we found 8 animal studies (lambs/pigs/ rats) [216][217][218][219][220][221][222][223] all demonstrating no advantage to 100% over 21% during CPR (very-low-quality evidence, downgraded for bias and indirectness).…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Animal evidence shows no advantage to 100% oxygen during CPR. [179][180][181][182][183][184][185][186] However, by the time resuscitation of a newborn infant has reached the stage of chest compressions, efforts to achieve return of spontaneous circulation using effective ventilation with low-concentration oxygen should have been attempted. Thus, it would appear sensible to try increasing the supplementary oxygen concentration.…”
Section: It Ismentioning
confidence: 99%
“…7,8 Although hypoxemia often prompts the administration of high concentrations of oxygen for infants with PPHN, a growing body of literature demonstrates that even brief periods of hyperoxia trigger oxidative stress as well as changes in enzyme activity and vascular reactivity. [9][10][11] Thus, new therapies are needed for newborns with PPHN.…”
Section: Persistent Pulmonary Hypertension Of the Newborn (Pphn)mentioning
confidence: 99%